The effect of inheritance of IgE responsiveness on the susceptibility of mice to Trichinella spiralis infection - Watanabe, Naohiro (Frontiers in Immunology, 2023)
IgE antibodies are likely involved in host protection. Trichinella spiralis is a helminth that induces protection through IgE antibodies. The present study examined T. spiralis susceptibility in high and low IgE responder mice, with a specific focus on the inheritance of IgE responsiveness, which controls IgE production specific for the IgE isotype and non-specific for antigens. Furthermore, low IgE responsiveness is inherited as a recessive trait under a single gene, which is not linked to the H-2 gene. This study determined the total IgE and anti-T. spiralis IgE antibody levels after T. spiralis infection in low IgE responder SJL/J mice were several times lower than those in high IgE responders, such as the BALB/c mice. An IgE-dependent susceptibility to T. spiralis, evaluated in mice treated with anti-IgE antibodies and in control mice, was observed in high IgE responder mice but not in low IgE responder mice. The inheritance of IgE responsiveness and susceptibility to T. spiralis was investigated using crosses of SJL/J with high IgE responders. All of the (BALB/c × SJL/J) F1 and half of the (BALB/c × SJL/J) F1 × SJL backcross progenies were high IgE responders after T. spiralis infection. Total IgE and antigen-specific IgE antibody levels were correlated and not linked to H-2. It should be noted that high IgE responders always exhibited low susceptibility, suggesting that the trait of IgE responsiveness functions as a trait of susceptibility to T. spiralis.